2015
DOI: 10.4155/fmc.15.161
|View full text |Cite
|
Sign up to set email alerts
|

ACAT1/SOAT1 as a Therapeutic Target for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common cause of dementia with no cure at present. Cholesterol metabolism is closely associated with AD at several stages. ACAT1 converts free cholesterol to cholesteryl esters, and plays important roles in cellular cholesterol homeostasis. Recent studies show that in a mouse model, blocking ACAT1 provides multiple beneficial effects on AD. Here we review the current evidence that implicates ACAT1 as a therapeutic target for AD. We also discuss the potential usage of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 137 publications
(162 reference statements)
2
68
0
Order By: Relevance
“…Our study is supported by the previously reported role of ACAT in modulating the intracellular cholesterol pool in various cell types: In macrophages (44) and in bone metastasisderived PC-3 cells (15), ACAT inhibition resulted in increased intracellular FC levels and decreased intracellular CE levels. In neurons, however, blocking ACAT1 activity suppressed CE synthesis without changing intracellular FC levels (16). Locally, CE is formed on the ER membrane where it modulates the function of ER resident ACATs and SREBP1 (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is supported by the previously reported role of ACAT in modulating the intracellular cholesterol pool in various cell types: In macrophages (44) and in bone metastasisderived PC-3 cells (15), ACAT inhibition resulted in increased intracellular FC levels and decreased intracellular CE levels. In neurons, however, blocking ACAT1 activity suppressed CE synthesis without changing intracellular FC levels (16). Locally, CE is formed on the ER membrane where it modulates the function of ER resident ACATs and SREBP1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACAT2-deficient mice are protected against diet-induced hypercholesterolemia due to a loss of cholesterol esterification activity in the intestine and liver (14). In addition, ACATs appear to play a key role in various diseases, such as cancer (15) and Alzheimer's disease (16,17). Despite this significant physiological importance of ACATs, their role in lipid metabolism in adipose tissue is still poorly understood.…”
mentioning
confidence: 99%
“…The massive accumulation of cholesteryl ester is observed in forebrain regions from mouse models or in patients with Alzheimer’s disease (AD) [37, 38], implying that SOAT1 is actively involved in amyloid-β synthesis and AD formation. SOAT1 is one of the targets that may have beneficial effects on AD when blocked [39], and we speculate miR-429-3p may have potential relationships associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cholesterol, SOAT can use multiple sterols as substrates and activators 3 . Because of its functional importance, SOAT1 is a potential drug target for Alzheimer’s disease 6 , atherosclerosis 7 and several types of cancers 811 .…”
Section: Mainmentioning
confidence: 99%